Adult learner responses to semi-autonomy in intensive ELT : a systematic replication case study - Hamilton-Turley, R. A. (Trinity College (Dublin, Ireland). School of Education, 2000)
The emerging field of classroom learner autonomy is defined by interest in complementing or replacing institutional group tuition, or 'other-directed learning' (ODL), with 'self-directed learning' (SDL). The enquiry addresses some of the conceptual, ethical, and practical questions implied by that interest, and reports the experimental introduction of SDL in an adult institution for English language teaching (ELT). It evaluates definitions of 'autonomy', proposes the concept of auto-responsible learning (ARL), and categorises ODL and SDL as dependent or independent on decision-making and action-taking criteria. It suggests for further research an SDL scale and grid, and appends a substantial corpus of class diary learner-English at nominal intermediate level from the first two experimental courses, with paracounselling notes included for the third course. Employing quantitative triangulation within a postpositivist replication case study paradigm, the enquiry investigated responses to classroom ODL or SDL on intensive ELT courses, for which the researcher acted as teacher/co-ordinator for the 15 months’ empirical period (814 contact-hours). Participants were daily exposed for four contiguous hours to both levels of the manipulated independent variable, learning mode, in the following mean ratios of ODL to SDL: Group A — 59:41; Group B — 53:47; Group C — 69:31.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin